P4 A prospective assessment of the clinical utility of intercostal artery identification in pleural intervention. (15th November 2016) - Talwar, A; Corcoran, JP; Hallifax, RJ; Wrightson, J; Psallidas, I; Rahman, NM
Abstract : Background: Respiratory Specialists perform an increasing number of complex pleural procedures. With this comes a greater focus on patient safety and risk reduction. There is strong evidence that ultrasound guidance in procedure site selection for pleural effusion reduces organ puncture and pneumothorax, but it remains important to choose intervention sites to avoid the intercostal arteries (ICA). Previous data suggest that the ICA can follow a tortuous course especially in the elderly. The use of colour Doppler to identify intercostal and collateral arteries has been shown to be accurate in research studies and may assist in selecting a safe intervention site. This study aimed to prospectively assess identification of the ICA in routine practice and the effect on procedure site selection. Methods: Data on identification of the ICA was prospectively collected as part of routine clinical care and documented in the pleural procedure records in a tertiary centre between July 2015 and July 2016. Successful identification of the ICA and its influence in choosing the procedure site was recorded. Results: 404 procedures were carried out over the study period. The mean age of the patients was 69.3 years (sd 14.2). Identification of the ICA was attempted in 386 (95.5%) procedures and the ICA was identified within the intercostal space in 192 (49.7%) of cases. The site of the procedure was altered after ICA detection in 56/192 (29.2%) of procedures and in 16/32 (50.0%) of image guided pleural biopsies. In 7/192 (3.6%) procedures the ICA was identified in all rib spaces at potential intervention sites, leading to the procedure not being attempted. No complications related to post procedure haemorrhage were reported. A more detailed analysis of the identification of the ICA and its influence on practice by procedure type is shown in Table 1 . Conclusion: Screening for the ICA in routine clinical practice influences procedural site selection. In some cases identification can result in abandoning a procedure, which may have led to intercostal bleeding. Patient position and potential rib crowding may explain differences in the rates of successful identification between procedures. If these findings are replicated in larger prospective studies, identification of the ICA may become routine practice to maximise safety.